Industry 4.0 and Its Relationship with Digital Transformation: A Systematic Literature Review 2019-2024 - Cardoso, Josiane de Fátima Daniel; Brum, Argemiro Luis (Revista de Administração da UFSM, 2025)
Purpose: This study aims to analyze the main concepts, benefits, and challenges related to Industry 4.0 and its relationship with Digital Transformation in the Brazilian industrial sector, based on a systematic literature review between 2019 and 2024. Methodology: The PRISMA protocol was used to conduct the systematic review, with searches in the Scopus, Web of Science, and SciELO databases, resulting in the selection of 42 articles. The analysis was guided by theoretical frameworks such as Verhoef et al. (2021), Schwab (2016), and Rogers (2019). Results: The findings demonstrate that Industry 4.0 has driven Digital Transformation through the adoption of technologies such as Big Data, IoT, cloud computing, and artificial intelligence. The studies highlight gains in efficiency, sustainability, and competitiveness, but also reveal gaps, such as adoption difficulties by small businesses and challenges in workforce reskilling. Social and Practical Implications: The research highlights the need for public incentive policies, continuous professional training, and technological integration strategies to enable digital transformation in various industrial sectors. Originality: The study contributes by consolidating an updated and systematized vision of the pillars of Industry 4.0 and the stages of Digital Transformation, in addition to identifying gaps and proposing an agenda for future research in the Brazilian industrial context.